The use of theory of planned behavior to systemically study the integrative-qualitative intentional behavior in Romanian preschool education with network analysis - Rad, Dana; Redeș, Adela; Roman, Alina; Egerău, Anca; Lile, Raul; Demeter, Edgar; Dughi, Tiberiu; Ignat, Sonia; Balaș, Evelina; Maier, Roxana; Kiss, Csaba; Mărineanu, Vasile; et al. (Frontiers in Psychology, 2023)
The objectives of this research is to develop and validate a scale to assess the integrative-qualitative intentional behavior (IQIB - ECEC) of preschool teachers in order to achieve SDG4.2's objective of ensuring that all children have access to high-quality pre-primary education. The literature on preschool inclusive and qualitative services was reviewed, and systematic field analysis in inclusive and high-quality early education settings was done as part of developing the rating scale. This research revealed that it is challenging to provide both an inclusive and high-quality educational environment for young children. The theory of planned behavior (TPB) describes key individual beliefs (attitudes, subjective norms, and perceived behavior control) that affect people's intentions to engage in a certain activity. TPB has been used as a framework in several research evaluating people's intentions to adopt a certain behavior as a result of its effective application to a variety of human activities. There hasn't been much effort put into developing a scale that may be used to examine one's own integrative-qualitative purposeful conduct when working with preschoolers. This research represents one of the first Romanian attempts to assess the competencies level of preschool teachers, after the enrolment in a National Training Program entitled Qualitative and Inclusive Early Childhood Education managed by the Romanian Educational Ministry. This study used a randomized 300 Romanian preschool teachers sample data collected via an online questionnaire. According to the validation study's findings, the measure is trustworthy and has a sound factor structure. Decision-makers are given discussion and ramifications. The main takeaway from this research is that theory-grounded data can provide information required to comprehend individual perspectives and develop appropriate intervention strategies on areas of expertise and attitudes that need further instilling, for the attainment of SDG4.2 goals by 2030, when developing behavioral interventions to address the increasing integrative-qualitative intentional behavior in preschool teachers.